Brexit and the United Kingdom's Devolutionary Constitution. (29th April 2022) - Masterman, Roger
Abstract: This piece considers the implications of the Brexit process for the United Kingdom's territorial constitution. It advances two narratives of the devolutionary settlement; one which emphasises the continuing post‐devolution influence – and dominance – of the institutions of UK‐level government, the other which regards devolution as having engineered a quasi‐federal division of powers and having diluted the sovereignty of the Westminster Parliament via expressions of national sovereignty in Scotland, Wales and Northern Ireland. The continuing resonance of the former is addressed across three elements of the Brexit process: (1) the design and outcome of the 2016 referendum; (2) litigation concerning Brexit and devolution; and (3) the legislative process of repatriating competences to domestic institutions from the EU. Seen through these lenses, Brexit is argued to provide ongoing evidence of the democratic deficits that the post‐1998 phase of devolution was designed to address, and of an increasingly unstable territorial constitution.